Ho Chi Minh's ideology on youth's role· how our Porty odopts ond opplies in on ero of strengthening industriolizotion ond modernizotion - Nguyễn Hữu Tài,; Lê Văn Công, (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
“A year starts from spring. A life starts from youth. Youth is the spring of society ”- President Ho Chi Minh's ideas about young people - the Party's successors, is an expression of the strategic vision with the inheritance force to build and protect Country. Inheriting and applying Ho Chi Minh's thought creatively about the young people’s role in the process of leading the country, our Party always appreciates the role and identifies that young people are the revolutionary strike force, HoChiMinh Communist Youth Union, the trusted reserve team of the Party; Works of Youth are vital issue for the nation.